Root and root canal morphology of third molars in a Jordanian subpopulation - Ibrahim Ali Ahmad; Manal Mahmoud Azzeh; Abdalwahab M.A. Zwiri; Mohd Ashraf Shakib Abu Haija; Maha Methqal Diab (Wolters Kluwer Medknow Publications, 2016)
Introduction: The aims of this study were to (1) investigate the root and root canal morphology of human third molars in a Jordanian subpopulation and (2) determine the effect of age, gender, and tooth location on the morphology of these teeth. Materials and Methods: A total of 159 maxillary and mandibular third molars were used in this study. After canal staining and tooth clearing, the specimens were examined, and the following morphological features were recorded: Number of roots and presence of roots fusion, number of canals and their configurations in each root, total number of canals per tooth, and incidence of lateral canals and intercanal communications. Results: The majority (74.2%) of maxillary molars had 3 roots and 3 (55.1%) or 4 (27%) canals while the majority (74.3%) of mandibular molars had 2 roots and 2 (38.6%) or 3 (45.7%) canals. Roots fusion was found in 70.1% of maxillary molars and 40.7% of mandibular molars. Type I canal configuration was the predominant type in distal roots of mandibular molars and distobuccal and palatal roots of maxillary molars. Multiple canals were evident in 36% of the maxillary mesiobuccal roots and 56% of mandibular mesial roots. Single/fused roots showed a wide range of canals number and configurations. The number of roots and canals in both molars did not differ with gender, age, and tooth location. Females had a higher incidence of roots fusion than males and this difference was significant in mandibular molars (P = 0.034). Conclusions: Third molars showed a range of root and canal morphologies. Careful preoperative assessment is essential before commencing root canal treatment on these teeth.